The Transition of Iraqi Refugees: A Study of Acculturation, Ethnic Retention, and Discrimination in Metropolitan Boston - Maruri, Swapna (Tufts Archival Research Center, 2005)
While media and academic sources alike have raised some concerns for the sustainability of the Iraqi refugee resettlement process in the United States, there still remain many important features of the Iraqi refugee experience that need to be addressed. 13 There was an initial focus on the refugee experience abroad followed by reports highlighted the difficulties refugees face in relation to financial standing. There has yet to be research about the sociology of the newly arrived Iraqi refugees’ acclimation to the United States and the specific environments in which they live, like the cities of Washington D.C., Los Angeles, and even Boston. This research expands on the journalistic depictions of this refugee experience by focusing on the social networking, acculturation, and ethnic retention of Iraqi refugees in the greater Boston area.